Suppression of Venturia inaequalis (apple scab) ascospore production using autumnapplied fungicides - Wood, P.N.; Beresford, R.M.; Taylor, T.J. (New Zealand Plant Protection, 2008)
In autumn 2006 apple leaves with visible scab (black spot) symptoms were collected at the time of leaf fall and dipped in fungicides at concentrations equivalent to field application rates The leaves were overwintered on gravel and ascospore production measured on three dates during the following spring using suction spore traps Of ten fungicides tested myclobutanil trifloxystrobin captan dodine tolyfluanid and cyprodinil either reduced or delayed ascospore production by Venturia inaequalis during the following spring compared with a waterdipped control Metiram dithianon urea and copper hydroxide had a minimal effect on ascospore production Leaves from a separate orchard trial produced significantly fewer ascospores after myclobutanil treatment than after captan treatment Captan and tolyfluanid are recommended for autumn application to control scab because they significantly reduced or delayed ascospore production and have a low risk of selecting resistant strains of V inaequalis Although also effective myclobutanil trifloxystrobin dodine and cyprodinil should not be used for autumn application because of the risk of fungicide resistance